STRATEGIES FOR SHARED SERVICE CENTRE - Ang, Yuen Ting (2010)
Since global economy downturn, governments all over the world faced mounting pressure over the increasing public service cost, and rising expectations for better and faster service from the citizens. Other factors such as rising health care costs with an aging population and technological advances also put a strain on the fiscal budget. Governments are expected to deliver more value with lesser and lesser budget in the midst of crisis after crisis. It is therefore a necessity for government to find means to reduce public service cost and increase the productivity. Globally, many governments have started to adopt matured concepts from the private sector to increase their productivity and to reduce cost, and among these concepts, shared services are gaining popularity in many public sector.